2018
DOI: 10.3233/mgc-180250
|View full text |Cite
|
Sign up to set email alerts
|

Selective separation of thorium from rare earth elements liquor during the alkaline processing of Egyptian monazite concentrate

Abstract: Monazite ore processing is a complicated matrix which is mainly attributed to the presence of high phosphate (25% of P 2 O 5 ) and sulfate concentration, hence, complicate the extraction and separation of REEs and other elements. Therefore, this work developed technical systematic studies for monazite processing using alkali solution, resulting in the removal and recovery of phosphate as a valuable product. Moreover, solvent extraction technique was used for selective separation of Th(IV) followed by the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Shahr El-Dina et al (2018) has successfully shown that 92.8% of P2O5 was removed from Egyption monazite using alkaline digestion. This high efficiency of phosphate removal may benefited the later rare earth and Th extraction process [13]. In this work, recent study are reported on the extraction of ThO2 from Malaysian monazite using alkaline digestion technique with caustic soda.…”
Section: Introductionmentioning
confidence: 98%
“…Shahr El-Dina et al (2018) has successfully shown that 92.8% of P2O5 was removed from Egyption monazite using alkaline digestion. This high efficiency of phosphate removal may benefited the later rare earth and Th extraction process [13]. In this work, recent study are reported on the extraction of ThO2 from Malaysian monazite using alkaline digestion technique with caustic soda.…”
Section: Introductionmentioning
confidence: 98%